Food, Eating, and Happy Aging: The Perceptions of Older Chinese People - Browning, Colette J.; Qiu, Zeqi; Yang, Hui; Zhang, Touhong; Thomas, Shane A. (Frontiers in Public Health, 2019)
China’s government and its people have for a long time focussed on food security for its population as one of the most important issues in economic and social development. Many older people in China have lived in times when food security was not stable. Thus, while food has a central position in Chinese culture for all Chinese people, it is of particular pertinence to older people. In this paper we explore the meaning of food and eating in the lives of older Chinese people and how it contributes to healthy, thus happy ageing. Focus groups and qualitative interviews were used in this study. Participants were recruited from the rural Yongfu Province of Southwest China, and the urban Fangzhuang and Haidan districts in Beijing. Forty-two participants were recruited aged 62 to 83 years of age. All focus groups and interviews were conducted in Mandarin and audiotaped with the participants’ permission. Audio-tapes were transcribed by a Chinese speaking researcher and then were translated into English. The initial analysis and interpretation were then presented and discussed at a workshop with all the authors. Two major themes emerged - the quantity of food and the quality of food required to have a happy old age. Participants discussed the desire to eat ‘until you are full’ because of their experiences of famine during childhood. However, they also believed that as an older person they should eat less for their health, particularly less high fat foods. The importance of the food quality and food affordability was also discussed. Grain and meat were characterized as ‘good’ foods and important in their diets for a happy old age. The participants, especially those from urban areas, were concerned with food safety. The high cultural importance of food for older Chinese was confirmed in this study. Social and economic lifespan experiences continue to impact on the food and eating attitudes and practices of older Chinese. The food related life experiences of older Chinese are quite different from younger Chinese and health promotion messaging needs to be informed by these unique perspectives in order to maximise its effectiveness.